A Comprehensive Review on the Versatile Applications of Ionic Liquids - Srinivasa Rao Aangothu; Sowjanya Prathipati; J. N. Pavan Kumar Chintala; Soumini C.; Hari Babu Bollikolla (Current Innovations in Chemical and Materials Sciences Vol. 4, 2024)
This review article highlights the various applications of Ionic liquids (IL) such as solvents, electrolytes, catalysis, solar cells, fuel cells, polymer science, food and bioproducts, lubricants, and many more ILs are also known as salts they are appropriate to below melting point and they can be also considered as a novel and extraordinary set of solvents. ILs are more than just green solvents and they showed interest in its practically exploding. They have established several applications and they synthesized water and air-stable ionic liquids based on an imidazolium cation like 1-alkyl-3-methylimidazolium and also tetrafluoroborate or hexafluorophosphate as the anion. The review is an attempt to make aware of the usage of Ionic liquids in various fields and think of the application of ILs in other fields also based on their properties. Finally, it is concluded that ILs have various applications in different fields such as use as solvents in various industries, electrolytes, heterogeneous catalysis, solar cells, fuel cells, polymer industry, food and bioproducts, and lubricants. However, some drawbacks with ionic liquids are highlighted concerning toxicity, preparation, and high cost in the process for use.